Examination of athletic best performance trends in track and field over one hundred years` history - Wei, R.; Liu, Y. (The Sport Journal, 2018)
It is always interesting to predict future performance and explore human limits. In this study, 24 events (running, jumping, and throwing) were studied from men`s and women`s track and field events. The best yearly performance data and world record data since 1900 to 2018 were collected. All the events were analyzed by applying longitudinal analysis with scatterplots. The findings revealed that it is encouraging to expect the new world record in men`s shorter running events and women`s longer running events. However, the waiting time for the new world records in men`s longer running events, women`s shorter running events, and both their field events will be much longer as going into the 21st century. For the overall track and field events, both men`s and women`s athletic performance may have reached the asymptotic level. Women`s athletic performances will not surpass men`s performances in track and field in the near future. To explore track and field performance trends and predict future world records, research of new methods and new prediction models are needed when the asymptotic level has been reached.